PENGARUH MEDIA RITATOON TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 12 TANJUNG BATU - Anisa Rahmawati; Allen Marga Retta; Puji Ayurachmawati (STKIP Subang, 2023)
The background of the problem in this study is the lack of learning outcomes in mathematics learning caused by the application of mathematical material using only student books without the help of other media. This study aims to determine the effect of using ritatoon media on the learning outcomes of third grade students at SD Negeri 12 Tanjung Batu. The research method used is the experimental method with a pretest-posttest control group design. The subjects of this study were students in class III A and III B of SD Negeri 12 Tanjung Batu, totaling 43 students. Methods of data collection using tests and documentation. The test instrument is in the form of multiple choice questions totaling 10 questions to measure student learning outcomes. Data analysis technique using Independent Sample T-test. The results showed that the influence of ritatoon media can improve elementary school students' learning outcomes in mathematics material which can be seen from the learning outcomes of hypothesis testing (Independent Sample T-Test) in the form of a significance value in this study, namely 0.000 > 0.05, which means Ho is rejected Ha is accepted. Keywords: ritatoon media, student learning outcomes